(untitled) (Trabalho & Educação, 2017)
Educational practices in prison contexts are submitted to particular tensions. The resocialization paradigms, based on the moral transformation of subjects deprived of liberty, may subordinate education to these objectives, infantilizing subjects who go through these institutional settings and enhancing the effects of self-mortification enhanced by Goffman, which characterizes these total institutions, including jail. Contrary to this possibility, other educational practices are possible in the liberating perspective which Freire conceived. In these contexts, these paradigms could help create opportunities for collective reflection on the living conditions that led these subjects to prison and possible ways to reduce the harm these institutions cause. ___ Las prácticas educativas en los contextos carcelarios están sujetas a tensiones particulares. Los paradigmas resocializadores, basados en la transformación moral de los sujetos privados de libertad, puede subordinar la educación a estos objetivos, infantilizando a los sujetos que transitan por estos escenarios institucionales y reforzando los efectos de mutilación del yo que Gofman destacó como propios de las instituciones totales, la cárcel entre ellas. Contra esta posibilidad, otras prácticas educativas son posibles, en la perspectiva liberadora que Freire concibió. En estos contextos, estos paradigmas podrían contribuir a establecer espacios de reflexión en torno a las condiciones de vida que llevaron a estos sujetos a la cárcel y las formas posibles de disminuir el daño que estas instituciones provocan.